Handgrip-Ring Structure Sensing Probe Assisted Multiple Signal Amplification Strategy for Sensitive and Label-Free Single-Stranded Nucleic Acid Analysis - Ying Ren; Yu He; Ping Li (Journal of Analytical Methods in Chemistry)
Precise and efficient identification of single-stranded nucleic acids is crucial for both pathological research and early diagnosis of diseases, such as cancers. Therefore, we have devised a novel biosensor that utilizes an elegantly designed handgrip-ring structure sensing probe to enhance the detection sensitivity and reduce background signals. The handgrip-ring structure sensing probe combines ring padlock-based target recognition and hairpin structure probe-based signal amplification. The target sequences form a binding interaction with the ring padlock in the sensing probe, leading to the elongation of the single-stranded chain with the assistance of polymerase. This elongation step results in the release of the hairpin probe, triggering a signal amplification process. This design significantly minimized the potential discrepancies that may occur during the signal amplification process, hence bestowing the approach with a low level of background signals. By utilizing this innovative design, the current biosensor demonstrates a remarkable ability to detect miRNA with a limit as low as 376 aM and single-stranded DNA sequences with a limit as low as 45.3 aM. In addition, it possesses exceptional discrimination capabilities. The efficacy of this approach in diagnosing targets was also effectively proved by the rational redesign of the ring padlock.